A skeleton‐less sponge of Caribbean mangroves: invasive or undescribed?. Issue 2 (23rd May 2013) - Alvizu, A.; Díaz, M.C.; Bastidas, C.; Rützler, K.; Thacker, R.W.; Márquez, L.M.
Abstract Recent surveys of sponges occurring on Caribbean mangrove roots demonstrated the presence of a skeleton‐less sponge of the genus Halisarca, very similar in its morphology to the temperate H. dujardinii. This study evaluated the possibility that the mangrove sponge was actually H. dujardinii that had been introduced into the Caribbean mangroves. Detailed histology revealed differences between the mangrove sponge and H. dujardinii in cuticle thickness, and in characteristics of the choanocytes, spherulous, and granular cells. Also, phylogenetic reconstruction and genetic distance estimates based on cytochrome oxidase I gene sequences clearly differentiated the mangrove Halisarca sp. from H. dujardinii. Therefore, we rejected the hypothesis of the invasion of H. dujardinii, recognizing instead the mangrove Halisarca sp. as a new species and naming it H. restingaensis sp. nov. Estimated levels of genetic variation in the ribosomal internal transcribed spacers indicated that populations of H. restingaensis sp. nov. are highly differentiated between Venezuela and Panama (Fst=0.71). This level of population differentiation is consistent with the short larval competence period that is common in members of the genus Halisarca.